Stable improvement in hand muscle strength in incomplete spinal cord injury patients by long-term paired associative stimulation—a case series study - Holopainen, Kirsi; Tolmacheva, Aleksandra; Bersch, Ines; Haakana, Piia; Pohjonen, Markus; Kirveskari, Erika; Arokoski, Jari; Shulga, Anastasia (Frontiers in Neurology, 2025)
IntroductionPaired associative stimulation (PAS) consists of high-intensity transcranial magnetic stimulation and high-frequency electric stimulation of the peripheral nerve (high-PAS) and can induce plastic changes in spared corticospinal connections in individuals with spinal cord injury (SCI), leading to the restoration of motor function. The objective of this study was to investigate the long-term effect of high-PAS on hand function and muscle strength.Materials and methodsHigh-PAS was applied to four patients with chronic, incomplete, cervical-level SCI multiple times a week for as long as hand muscle strength improved. The median, ulnar, and radial nerves of one hand chosen by the patient were stimulated. Patients underwent Medical Research Council (MRC) manual muscle testing monthly during the stimulation period and were followed for 12 months after the stimulation.ResultsStrength increased in both the stimulated and non-stimulated hands. In muscles innervated by stimulated nerves, strength increased on average by 24.5% from pre- to post-conditions (p = 0.013). The achieved strength level was maintained for a minimum of 6 months after completing the stimulations. Patients were also evaluated with motor point (MP) integrity testing to estimate the extent of lower motor neuron damage. High MP integrity testing scores (low extent of damage) correlated positively with good MRC outcomes of the stimulated hand after high-PAS (r = 0.52, p ≤ 0.001).ConclusionHigh-PAS may improve muscle strength of both the stimulated and contralateral sides. Stable results were achieved when stimulation was delivered as long as MRC score improved progressively. The optimal duration of high-PAS treatment remains unknown.Clinical trial registrationclinicaltrials.gov, identifier NCT03045744.